Obtaining and Interpreting Eyewitness Identification Test Evidence: The Influence of Police–Witness Interactions - Brewer, Neil (2009)
Eyewitnesses to a crime are frequently asked to view an identification parade to see if they can identify the offender. Conduct of a line-up involves police or line-up administrators in a number of important decisions, such as who to put in the line-up, the method of presentation of the line-up, and what to say to witnesses before and after the line-up. The identification test can be conceptualized as a variant on an interview between the police and the witness, involving important interactions between police (or other line-up administrators) and witnesses. These interactions can profoundly influence witness decisions and impact on the characteristics of any subsequent evidence they provide in the courts. We shall focus on (i) the expectations that police/administrators can engender in witnesses and how these can shape witness behaviour; (ii) the instructions that are provided to witnesses prior to viewing the line-up; (iii) possible ways in which administrators can interact with (and hence influence) witnesses in the conduct of line-ups; (iv) the soliciting of confidence assessments from witnesses; (v) the interpretation of witness confidence assessments; and (vi) the influence of interactions that occur post - identification on witnesses’ subsequent reports about the event and the identification test